(untitled) (Global Journal of Science Frontier Research, 2017)
Baseline geochemical assessment of an area within latitude 006o431N and 003o441N and longitude 003o311E and 003o371E was carried out in other to provide information on the rate of contamination/ pollution caused to the soils by the iron and steel industries` activities around Ikorodu area. 11 soil samples were collected, prepared and analysed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Interpretation of the analysis results was carried out for their metal contents. Lead has the highest concentrations in soils (9945ppm) while Manganese was the most widely distributed metal in the area of study with a mean concentration value of 8414ppm. Further geochemical evaluation of the soils using Geo-accumulation Index, Enrichment Factor, Contamination Factor, and Pollution Load Index, revealed significant concentration of lead and zinc in the environmental media from within the study area while the other elements have minimal concentration in the environmental media studied. The Enrichment Factor calculated also showed extremely high enrichment of lead in the soils of the study area (621). The contamination factor calculated showed that Pb and Zn are the elements contaminating the soils mostly. While zinc moderately contaminated the soil of the study area with a contamination factor of 4, lead extremely contaminated the soil with a contamination factor of 89. The other elements showed less contamination of the soils of the study area. The Pollution Load Index (PLI) showed the soils of the study area are not highly polluted (PLI